Research progress of bone metastases: From disease recognition to clinical practice - Yang, Wenbo; Pan, Qing; Huang, Fuhua; Hu, Hongzhi; Shao, Zengwu (Frontiers in Oncology, 2023)
Bone metastases, as one of the common types of metastatic tumors, have a great impact on the survival period and quality of life of patients. Bone metastases are usually characterized by bone destruction. Skeletal related events caused by bone destruction often lead to pain, pathological fractures and even paralysis. In this review, we provide a detailed explanation of bone metastases from the epidemiology, clinical features, pathogenesis, and recently developed clinical treatment viewpoints. We concluded that the incidence of bone metastases is increasing gradually, with serious clinical symptoms, complex pathogenesis and diverse clinical treatment. Tumor cells, immune cells, osteoblasts/osteoclasts and other cells as well as cytokines and enzymes all play a key role in the pathogenesis of bone metastases. We believe that the future treatment of bone metastases will be diversified and comprehensive. Some advanced technologies, such as nanomedicine, could be used for treatment, but this depends on understanding how disease occurs. With the development of treatment, the survival time and quality of life of patients will be improved.